(untitled) (Journal of Medical & Health Sciences Review, 2025)
Every year, millions of people suffer from food-borne illnesses which are primarily caused by lack of food safety knowledge, attitude and practices among food vendors (KAP model). The aim of this study is to assess these parameters in food vendors in different areas of Rawalpindi. A semi-structured questionnaire which covered all these attributes was used to collect responses from food vendors (n=59). The results showed that most food vendors had adequate knowledge regarding food safety, but perceived knowledge failed to be translated into practices. In conclusion, this lack of implementation needs to be addressed in order to improve food safety among food vendors in different areas of Rawalpindi.